Perestroika and the party national and transnational perspectives on European communist parties in the era of Soviet reform - Di Palma, Francesco 1980- (Berghahn, 2019)
Perestroika and the Party -- Contents -- Introduction -- Part I. Eastern Europe -- Chapter 1. The Impact of Perestroika and Glasnost on the CPSU's Stance toward the "Fraternal Parties" in the Eastern Bloc -- Chapter 2. Soviet Society, Perestroika, and the End of the USSR -- Chapter 3. Perestroika Made in Hungary? -- Chapter 4. Yugoslavia and Perestroika, 1985-1991 -- Chapter 5. The Polish United Workers' Party and Perestroika -- Chapter 6. SED and Perestroika -- Chapter 7. Between External Constraint and Internal Crackdown -- Part II. Western Europe -- Chapter 8. Parallel Destinies -- Chapter 9. "I Felt as If I Were Faced with a French Honecker" -- Chapter 10. A Dialogue of the Deaf -- Chapter 11. Premature Perestroika -- Chapter 12. Perestroika and the Greek Left -- Chapter 13. The Austrian Communists and Perestroika -- Chapter 14. The Spanish Communist Party and Perestroika -- Afterword. Gorbachev and the End of International Communism -- Index.